2018
DOI: 10.3762/bjoc.14.123
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of trifluoromethylated 2H-azirines through Togni reagent-mediated trifluoromethylation followed by PhIO-mediated azirination

Abstract: The reaction of enamine compounds with the Togni reagent in the presence of CuI afforded β-trifluoromethylated enamine intermediates, which were converted directly to biologically interesting trifluoromethylated 2H-azirines by an iodosobenzene (PhIO)-mediated intramolecular azirination in a one-pot process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 69 publications
0
2
0
1
Order By: Relevance
“…2017 年, 江焕峰课题组 [30] 报道了一种在烯胺酮的 三氟甲基化方法(Scheme 15). 该方法使用三氟甲基磺 酸钠为三氟甲基源, 以叔丁基过氧化氢(TBHP)为氧化 剂, 在 DMF 中, 50 ℃下, 搅拌 12 h, 可以中等产率得到 同年, 阳华课题组 [31] 2018 年, 杜云飞课题组 [32] 报道了一种 Togni 试剂介…”
Section: 三氟甲基化unclassified
“…2017 年, 江焕峰课题组 [30] 报道了一种在烯胺酮的 三氟甲基化方法(Scheme 15). 该方法使用三氟甲基磺 酸钠为三氟甲基源, 以叔丁基过氧化氢(TBHP)为氧化 剂, 在 DMF 中, 50 ℃下, 搅拌 12 h, 可以中等产率得到 同年, 阳华课题组 [31] 2018 年, 杜云飞课题组 [32] 报道了一种 Togni 试剂介…”
Section: 三氟甲基化unclassified
“…Another study by same group reported the synthesis of trifluoromethylated 2 H ‐azirines. In this one‐pot process, the enamine compound reacts with Togni reagent in the presence of CuI to obtain the intermediate β‐trifluoromethylated enamine, which was converted to trifluoromethyl 2 H ‐azirine in the presence of PhIO (Scheme 69) [92].…”
Section: Oxidative Cyclization Of Enamine Derivativesmentioning
confidence: 99%
“…Among various fluorine containing substituents, the trifluoromethyl group (CF 3 ) is highly valuable for applications in drug discovery, as the incorporation of this substituent often significantly improves the lipophilicity, bioavailability and protein-binding affinity of a molecule and suppresses metabolic detoxification processes to increase the in vivo lifetime of a drug. 5 Therefore, the development of efficient and versatile strategies for introducing the CF 3 moiety into various organic molecules has become one of the hottest topics in advanced organic synthesis in recent years. 6 Among the many methods developed, particularly noteworthy is the vicinal halotrifluoromethylation of alkenes due to its high pot- and step-economy for the introduction of two versatile functional groups ( i.e.…”
Section: Introductionmentioning
confidence: 99%